2004
DOI: 10.1200/jco.2004.05.113
|View full text |Cite
|
Sign up to set email alerts
|

FOLFIRI Followed by FOLFOX6 or the Reverse Sequence in Advanced Colorectal Cancer: A Randomized GERCOR Study

Abstract: Both sequences achieved a prolonged survival and similar efficacy. The toxicity profiles were different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

72
1,639
12
84

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 2,696 publications
(1,807 citation statements)
references
References 24 publications
72
1,639
12
84
Order By: Relevance
“…However, the relative efficacy of these two regimens was directly compared in the randomised Tournigand trial (Tournigand et al, 2004). Although this study was primarily designed to investigate whether the sequence of administration of FOLFOX and FOLFIRI was important in terms of second PFS (the time from randomisation until disease progression after second-line therapy), it provides an important insight into the relative efficacies of these combinations in both the first-and second-line settings.…”
Section: Relative Efficacy Of First-line Combinationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the relative efficacy of these two regimens was directly compared in the randomised Tournigand trial (Tournigand et al, 2004). Although this study was primarily designed to investigate whether the sequence of administration of FOLFOX and FOLFIRI was important in terms of second PFS (the time from randomisation until disease progression after second-line therapy), it provides an important insight into the relative efficacies of these combinations in both the first-and second-line settings.…”
Section: Relative Efficacy Of First-line Combinationsmentioning
confidence: 99%
“…Oxaliplatin/5-FU/FA has been shown to prolong disease-free survival in patients undergoing curative resection for stage II and III CRC compared with 5-FU/FA alone (Andre et al, 2004), and has consequently been approved for the adjuvant therapy of patients with stage III CRC. It is likely that this will in turn lead to the increased use of irinotecan/5-FU/FA first-line for advanced disease.…”
Section: Choice Of First-line Treatment Following Adjuvant Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, regimens combining FU with IRI or l-OHP are equally effective in terms of response rate and overall survival (Tournigand et al, 2004) and represent the standard first-line treatment in advanced CRC (O'Neil and Goldberg, 2005). Although three combinations of IRI and FU (IFL, FOLFIRI and AIO þ IRI) have been evaluated in phase III studies (Saltz et al, 2000;Douillard et al, 2000;Köhne et al, 2005), several other schedules have been proposed (Venook, 2005;Atalay et al, 2003).…”
mentioning
confidence: 99%
“…The toxicity reported in the American studies was partially due to the different delivery schedule of CPT-11/LV/5-FU, and in a study in which CPT-11 was administered on a weekly basis, diarrhoea was reported in 88.9% of patients (Douillard et al, 2000). A recently published randomised phase III study has investigated the efficacy of the alternate sequence of administration of the FOLFIRI and FOLFOX regimens in the treatment of MCC (Tournigand et al, 2004). Second-line treatment with FOLFIRI achieved a 4% response rate with a 2.5 month median progression-free survival rate and overall survival of 20.6 months from the start of FOLFOX administered as first-line chemotherapy.…”
Section: Months)mentioning
confidence: 99%